Therapy discontinuation in a primary care psychological service: why patients drop out. (2020) - Ghaemian, Aisan; Ghomi, Mahdi; Wrightman, Miles; Ellis-Nee, Colm
Abstract: The present study aimed to explore patients' experience with an Improving Access to Psychological Therapies (IAPT) service, and to investigate the reasons for discontinuing their treatment. A qualitative approach was adopted using thematic analysis of semi-structured interviews carried out with 818 patients attending for treatment in Talking Change from November 2015 to January 2019, retrospectively. The five main themes that emerged from the study were: 'Felt better', 'Issues with group settings', 'Therapeutic alliance breakdown', 'Miscommunication' and 'Impracticalities'. The qualitative study uncovered a wide range of reasons for people who had dropped out from their treatment. The findings mainly emphasised general dissatisfaction and inconvenient appointments. However, improvement in symptoms of depression and anxiety was also identified as a key factor among patients who discontinued their treatment. This recovery is known as 'progress withdrawal' in which patients withdraw from treatment early due to good therapeutic progress. We present clinical and procedural implications arising from these themes. Key learning aims: (1) To explore what can cause discontinuation of therapy. (2) To obtain the experience of people who have received treatment and dropped out from Talking Change Psychological Therapy services. (3) To explore whether people recovered as part of the treatment withdrawal and what may have helped towards that recovery.